Calculation of Tyre Pyrolytic Oil Combustion Products Using the Method of Gibbs Free Energy Minimization - Gamboa, A. R. [UNESP]; De Carvalho, J. A. [UNESP]; Rocha, A. M.A. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper presents a practical and economical method of calculation based on thermodynamic equilibrium, which allows to evaluate quantitatively and qualitatively the emissions of combustion products of alternative fuels in search state, such as tyre pyrolytic oil which can be used in equipment such as compression ignition engine, boilers, furnaces and gas turbine combustion chambers.
Keywords: chemical equilibrium; combustion; Gibbs free energy; tyres